Attitudes Towards Artificial intelligence Among Dermatologists Working in Saudi Arabia - Al-Ali, Fatima; Polesie, Sam; Paoli, John; Aljasser , Mohammed; Salah, Louai (Dermatology Practical & Conceptual, 2023)
Introduction: Artificial intelligence (AI) and its application are one of the most discussed modern technologies nowadays. With the rapid use of AI in medicine, and specifically in dermatology, only a few studies have studied the attitude of physicians toward AI. Objective: To recognize the attitudes towards AI among dermatologists in the Kingdom of Saudi Arabia. Methods: A cross-sectional survey was done among dermatologists in Saudi Arabia. Questionnaires were distributed through several online channels. Results: Overall, 103 dermatologists filled out the survey. The majority saw very strong or strong potential for AI in automated detection of skin diseases based on dermatological clinical images (50.9%), dermoscopic images (66.6%), and within dermatopathology (66.6%). In regard to results of attitudes towards AI, 56.6% and 52. 8% agreed that AI will revolutionize medicine and dermatology, respectively. However, many of the respondents disagreed that AI will replace physicians (41.5%) and human dermatologists (39.6%) in the future.. Age did not impact the overall attitude of dermatologists. Conclusion: Dermatologists in Saudi Arabia showed an optimistic attitude towards AI in dermatology and medicine. However, dermatologists believe that AI will not replace humans in the future.